Accuracy, limitations and cost efficiency of eDNA‐based community survey in tropical frogs. (29th August 2018) - Bálint, Miklós; Nowak, Carsten; Márton, Orsolya; Pauls, Steffen U.; Wittwer, Claudia; Aramayo, José Luis; Schulze, Arne; Chambert, Thierry; Cocchiararo, Berardino; Jansen, Martin
Abstract: Rapid environmental change in highly biodiverse tropical regions demands efficient biomonitoring programmes. While existing metrics of species diversity and community composition rely on encounter‐based survey data, eDNA recently emerged as alternative approach. Costs and ecological value of eDNA‐based methods have rarely been evaluated in tropical regions, where high species richness is accompanied by high functional diversity (e.g., the use of different microhabitats by different species and life stages). We first tested whether estimation of tropical frogs' community structure derived from eDNA data is compatible with expert field assessments. Next, we evaluated whether eDNA is a financially viable solution for biodiversity monitoring in tropical regions. We applied eDNA metabarcoding to investigate frog species occurrence in five ponds in the Chiquitano dry forest region in Bolivia and compared our data with a simultaneous visual and audio encounter survey (VAES). We found that taxon lists and community structure generated with eDNA and VAES correspond closely, and most deviations are attributable to different species' life histories. Cost efficiency of eDNA surveys was mostly influenced by the richness of local fauna and the number of surveyed sites: VAES may be less costly in low‐diversity regions, but eDNA quickly becomes more cost‐efficient in high‐diversity regions with many sites sampled. The results highlight that eDNA is suitable for large‐scale biodiversity surveys in high‐diversity areas if life history is considered, and certain precautions in sampling, genetic analyses and data interpretation are taken. We anticipate that spatially extensive, standardized eDNA biodiversity surveys will quickly emerge in the future.